A study to investigate the key sources of odors in Al-Multaqa Village, Sultanate of Oman. Issue 1 (2nd January 2017) - Abdul-Wahab, Sabah; Al-Rawas, Ghazi; Charabi, Yassine; Al-Wardy, Malik; Fadlallah, Sulaiman
ABSTRACT: Al-Multaqa Village, located in the province of Al-Amerat, Sultanate of Oman, has experienced a serious situation with odors. Residents of the village have complained about strong odors at night and in early morning for the past two years. Four potentially odor-emitting facilities are located near the village: the SITA & Al-Bashaer Environment (Suez Environment) landfill and leachate pond, Haya's biosolids composting plant, and Be'ah's medical waste treatment facility. This study concentrates on investigating and clarifying which of these facilities is the key contributor to the odor issue in the Al-Multaqa region. The CALPUFF Modeling System was used to model and simulate the dispersion of odors throughout the year. The odor emissions from Be'ah's medical waste treatment plant were below the complaint threshold; therefore, the facility was found not to be a major source of odor. For the three remaining facilities, CALPUFF simulation results revealed that they were major contributors to the odor issue at Al-Multaqa as all three facilities violated the complaint threshold of 5 odor units (OU). Of the four facilities, the landfill was responsible for the greatest contribution. The leachate pond and the composting plant contributed almost equally under peak conditions on most of the modeling days set in this study. It was determined that measures must be taken in order to solve the odor issue and prevent future incidents in the region.